Decreased levels of PSD95 and two associated proteins and increased levels of BCl2 and caspase 3 in hippocampus from subjects with amnestic mild cognitive impairment: Insights into their potential roles for loss of synapses and memory, accumulation of Aβ, and neurodegeneration in a prodromal stage of Alzheimer's disease - Sultana, Rukhsana; Banks, William A.; Butterfield, D. Allan (Journal of neuroscience research, 2010)
Alzheimer's disease (AD) is the most common form of dementia and is pathologically characterized by senile plaques, neurofibrillary tangles, synaptic disruption and loss, and progressive neuronal deficits. The exact mechanism(s) of AD pathogenesis largely remain unknown. With advances in technology diagnosis of a pre‐AD stage referred to as amnestic mild cognitive impairment (MCI) has become possible. Amnestic MCI is characterized clinically by memory deficit, but normal activities of daily living and no dementia. In the present study, compared to controls, we observed in hippocampus from subjects with MCI a significantly decreased level of PSD95, a key synaptic protein, and also decreased levels of two proteins associated with PSD95, the N‐methyl‐D‐aspartate receptor, subunit 2A (NR2A) and the low‐density lipoprotein receptor‐1 (LRP1). PSD95 and NR2A are involved in long‐term potentiation, a key component of memory formation, and LRP1 is involved in efflux of amyloid beta‐peptide (1‐42). Aβ (1‐42) conceivably is critical to the pathogenesis of MCI and AD, including the oxidative stress under which brain in both conditions exist. The data obtained from the current study suggest a possible involvement of these proteins in synaptic alterations, apoptosis and consequent decrements in learning and memory associated with the progression of MCI to AD. © 2009 Wiley‐Liss, Inc.